Gonadotrophins Versus Clomifene Citrate With or Without Intrauterine Insemination in Women With Normogonadotropic Anovulation and Clomifene Failure (M-OVIN): A Randomized, Two-by-Two Factorial Trial. Issue 5 (May 2018) - Weiss, Nienke S.; Nahuis, Marleen J.; Bordewijk, Esmee; Oosterhuis, Jurjen E.; Smeenk, Jesper M. J.; Hoek, Annemieke; Broekmans, Frank J. M.; Fleischer, Kathrin; de Bruin, Jan Peter; Kaaijk, Eugenie M.; Laven, Joop S. E.; Hendriks, Dave J.; et al.
Abstract : (Abstracted from Lancet 2018;391:758–765) Clomifene citrate has long been used as a first-line ovulation induction agent for women wishing to conceive who have normogonadotropic anovulation (absent or irregular ovulation). Women who ovulate but do not conceive after several cycles with clomifene citrate are usually switched to ovulation induction with gonadotrophins, with or without intrauterine insemination.